THE IMPACT OF INJURY IN WELSH PROFESSIONAL RUGBY. Issue 7 (11th March 2014) - Moore, I; Mathema, P; Ranson, C
Abstract : Background: A detailed understanding of injury types and rates is needed to inform effective injury prevention and management. This is the first comprehensive injury surveillance report across the four Welsh Rugby Union (WRU) Region Professional Teams. Objective: To identify priority injury problems and potential risk factors across the WRU Regions. Design: A designated medical team member from each Region recorded; all time-loss injuries, training and match exposure during the 2012–2013 domestic season. Consensus injury surveillance (Fuller et al., 2007) methods were used for data analysis. Setting: Top tier Welsh professional rugby. Participants: All players (173) from the four WRU Region clubs during the 2012–2013 season. Risk factor assessment: The relationships between; injury rates, types and severity, and mechanism of injury, player age and activity (training or match) at time of injury. Main outcome measurement: Training and match Injury incidence (per 1000 hours), injury prevalence (% of players unavailable) and average days-lost per injury were calculated for each variable. Results: Overall injury incidence was 10/1000 hrs (2/1000 training hrs, 98/1000 match hrs), prevalence was 18% and days-lost per injury was 26. Acute strain/sprain and impact injuries had the highest injury incidence and prevalence (3–4/1000 hrs and 6–8%). Older players (>24 years) had higher; injury incidence (6 vs. 4 for younger players), injury prevalence (11 vs. 8%) and more days lost per injury (27 vs. 24). The majority of match injuries occurred during tackles (63%). Strength training and running caused the greatest number of training injuries, with strength training injuries resulting in longer periods out (49 vs. 34 days lost per running injury). Conclusions: Prevention strategies should target the high rate of match injuries.Older players may require bespoke injury risk management, and exposure to contact events (particularly tackles) needs to be recorded to ascertain the specific activity risk.